ORGANIZATION HARDWARE AND SOFTWARE AUTOMATED SYSTEMS OF TANK PARKS LIQUID HYDROCARBONS - Заміховський, Леонід Михайлович; Николайчук, Микола Ярославович; Мойсюк, Юрій Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Through the analysis of processes of reservoir parks defined process parameters to calculate the volume and mass of liquid hydrocarbons. A functional, algorithmic and software solutions for implementing the system of tank parks based on hardware and software Simatic S7. The peculiarity of the proposed system is the newest element and software base (PLC Simatic S7-1200, SCADA WinCC), and the possibility of remote monitoring and management of geographically distributed objects via WEB-interface.